STRATEGI PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA UNTUK MEMBANGUN ATTITUDE ANAK 6–12 TAHUN - Jannes Eduard Sirait; Rosmawati Citra Kharisma Cibro; Sadrakh Sugiono; Johni Hardori (Edukasi : Jurnal Pendidikan Agama Kristen, 2023)
Christian Religious Education (CRE) within the family plays a central role in shaping the attitudes of children aged 6–12 years. At the stage of concrete-operational cognitive development, children begin to understand values, rules, and role models instilled in everyday life. This study aims to analyze the strategies of Christian families in nurturing children’s attitudes through the teaching of Scripture, exemplary living, spiritual discipline, and loving communication. The research method employed is a literature study with a descriptive-analytical approach. The findings indicate that CRE in the family significantly contributes to the formation of Christian character in children, particularly in aspects of obedience, empathy, honesty, and responsibility. This article recommends that Christian families consistently practice faith-based habits and foster healthy relationships so that children’s attitudes grow in harmony with Christian values.